Yield-Water-Nitrogen Response Analysis in Coriander - Singh, S D; Rao, J S (Annals of Arid Zone, 2016)
A field study on the response of coriander (Coriolldnlln soil L.) to irrigation and nitrogen was made for two years at the Ccntral Arid Zone Rescarch Institutc', Jodhpur. A 2- factor central composite rotatable design with water and N each at predetermined values -1.414, -I, 0, I and 1.414 was used. Thc actual values, in order of their predetermined levels, were 120, 180. 340, 490 and 550 mm of water and 0, 18, 60, 102 and 120 kg N ha-1. However. interactivc cffects of water and N were examined at their equispaced levels. The highcr watcr supplies imposed greater demand on applied N. The nitrogen optima werc 36. 62. 88, 114 and 140 kg ha-1 for the 120, 240, 360, 480 and 600 mm of water supplies, respeetivcly. Nitrogen at 140 kg ha-1 and water level at 600 mm were beyond the cxpcrimental range, and therefore the treatmcnt combining 480 mm of irrigation water and 114 kg N ha-1 cmerged as the optimal package to produce the seed yield of 2366 kg ha,l. However, the combination of 490 mm of water and 93 kg. N ha-1 would cost least to the farmcr for a yield goal set to 2300 kg ha-1, which was identical to optimal yield.